THE CRYSTAL AND MAGNETIC-STRUCTURES OF BA3NIRU2O9, BA3CORU2O9, AND BA3ZNRU2O9 - Lightfoot, P; Battle, P (1990)
The crystal structures of the 6H perovskites Ba3NiRu2O9, and Ba3CoRu2O9 have been refined from neutron powder diffraction data collected at 5 or 2 K. Ba3NiRu2O9 and Ba3ZnRu2O9 have hexagonal symmetry, space group P63 mmc: aNi = 5.7256(2). cNi = 14.0596(2) Å; aZn = 5.7549(2), cZn = 14.1328(2) Å. Ba3CoRu2O9 undergoes a phase transition from hexagonal symmetry at room temperature to orthorhombic symmetry at 2 K, space group Cmcm: aCo = 5.7456(1), bCo = 9.9177(2), cCo = 14.0862(3) Å. In all three compounds the cation sites within the face-sharing octahedra of the 6H structure are occupied by Ru5+; the corner-sharing octahedra are occupied by Zn2+, Ni2+, or Co2+. The neutron diffraction data show that Ba3NiRu2O9 is magnetically ordered at 5 K, with antiferromagnetic coupling between Ru5+ ions in the Ru2O9 dimers and ferromagnetic coupling along approximately linear Ni2+ORu5+ superexchange pathways. The magnetic moments align along z. Ba3CoRu2O9 is also magnetically ordered with antiferromagnetic coupling in the Ru2O9 dimers, but in this case antiferromagnetic superexchange between Co2+ ions leads to a more complex magnetic structure. © 1990.